Kritik Pemerintah Pada Lagu “Gugatan Rakyat Semesta” Karya Feast; Analisis Wacana Kritis Norman Fairclough - Frima, Mohammad Syafa; Mayasari, Mayasari; Lubis, Fardiah Oktariani (Universitas Muhammadiyah Sumatera Utara, 2024)
This research aims to examine the meaning of a song as a tool for criticism, focusing on